Estimation of Biological Ages with Kvaal Method Using Panoramic Radiography in Semarang City - Niluh Ringga Woroprobosari; Nurul Rezki Utami; Eko Hadianto (Denta Journal Kedokteran Gigi, 2020)
Introduction: Forensic odontology is a branch of dentistry that has disciplines learn about the examination of evidence derived from teeth, and how to deal with the evidence for legal concerns. Purpose: The aim of the study was to describe biological age estimates by using Kvaal method in Semarang, and the difference between biological and chronological age by using the Kvaal method in Semarang. This study was descriptive with crosssectional design. Materials and Methods: One of the methods in determining the estimated age by using teeth is the Kvaal method. Kvaal method determines the estimated age based on the pulp size using radiography. Result: The results showed the difference between biological and chronological age was ±4,57 years. This result is lower than Kvaal’s previous study result which was ±9,5 years. Conclusion: Based in the findings above, it can be concluded that the difference of chronological and biological age using Kvaal method in Semarang was ±4,57 years within 15-60 years old individuals in Semarang.